CONCRETE POLYTOPES MAY NOT TILE THE SPACE. Issue 4 (16th July 2020) - Garber, Alexey; Pak, Igor
Abstract: Brandolini et al . conjectured in ( Preprint, 2019) that all concrete lattice polytopes can multitile the space. We disprove this conjecture in a strong form, by constructing an infinite family of counterexamples in  R 3 .